Colistin Resistance Among Multiple Sequence Types of Klebsiella pneumoniae Is Associated With Diverse Resistance Mechanisms: A Report From India - Azam, Mudsser; Gaind, Rajni; Yadav, Gulshan; Sharma, Amit; Upmanyu, Kirti; Jain, Manisha; Singh, Ruchi (Frontiers in Microbiology, 2021)
Background: The resistance to colistin and carbapenems in Klebsiella pneumoniae infections have been associated with increased morbidity and mortality worldwide. A retrospective observational study was conducted to determine the prevalence and molecular events contributing to colistin resistance. Methods: Clinical samples were screened for colistin resistance and underlying mechanisms were studied by PCR-based amplification and sequence analysis of genes of two-component regulatory system (phoPQ and pmrAB), regulatory transmembrane protein-coding mgrB, and mobilized colistin resistance genes (mcr-1-8). Gene expression of pmrC and pmrK was analyzed by qRT-PCR, and the genetic relationship was assessed by MLST. The putative effect of amino-acid substitutions was predicted by a combination of bioinformatics tools. Results: Of 335 Klebsiella spp. screened, 11 (3.2%) were identified as colistin-resistant (MIC range, 8 to >128 μg/ml). K. pneumoniae isolates belonged to clonal complex-11 (CC11) with sequence types (STs): 14, 16, 43, 54, 147 and 395, whereby four isolates conferred three novel STs (3986, 3987 and 3988) profiles. Sequence analysis revealed non-synonymous potentially deleterious mutations in phoP (T151A), phoQ (del87–90, del263–264, L30Q, and A351D), pmrA (G53S), pmrB (D150V, T157P, L237R, G250C, A252G, R315P, and Q331H), and mgrB (C28G) genes. The mgrB gene in three strains was disrupted by insertion sequences encoding IS1-like and IS5/IS1182 family-like transposase genes. All 11 isolates showed an elevation in the transcription level of pmrC gene. Mobilized colistin-resistance (mcr) genes were not detected. All but one of the colistin-resistant isolates was also resistant to carbapenems; β-lactamase genes blaNDM-1-like, blaOXA-48-like, and blaCTX-M-like were detected in eight, five, and nine isolates, respectively. Conclusion: All the studied colistin- and carbapenem-resistant K. pneumoniae isolates were genetically distinct, and various mechanisms of colistin resistance were detected, indicating its spontaneous emergence in this bacterial species.